Sistem Interkoneksi Data Antar Unit Guna Mendukung Keberhasilan Akreditasi Program Studi Pada Fakultas Teknik UNS - widodo, purwadi joko; Setiono, Setiono; Diharjo, Kuncoro; Marwoto, Sofa (Jurnal Sistem Komputer, 2013)
The research was carried out in order to build a web-based computer application systems to support the smooth process of accreditation of study programs by BAN PT at the Faculty of Engineering, University Eleven March Surakarta. It is planned to build a system that support the accreditation process of study programs, particularly in preparation of Borang Akreditasi. The system was built for the purpose of a database system to accommodate the extraction data from administrative units in the Faculty of Engineering, University Sebelas Maret Surakarta. Development of systems and applications is done using open-source software Linux-Ubuntu Server operating system, the MySQL database server, and PHP as programming language. The end result of this engineering-research is developed a system that can support the implementation of the accreditation in the Faculty of Engineering Universitas Sebelas Maret Surakarta.